Self-assembled binary structures of Fe(III) and metal-free porphyrins for solar light-assisted catalytic hydrogenation of 4-nitrophenol. (November 2022) - Corrêa, G.A.; Loureiro, M.P.; Kuźniarska-Biernacka, I.; Freire, C.; Rebelo, S.L.H.
Abstract: Eco-sustainable reduction reactions using nontoxic and non-noble metal-based materials can be inspired on biomimetic catalysis although their development remains a challenge. In this work, nanostructured materials carrying Fe(III) porphyrins have been prepared by ionic self-assembly in water and tested in the mimics of the six electron reduction activity of nitrite reductase, in the presence of NaBH4 . A structuring effect is observed in solar light-assisted conditions. For materials built with two oppositely charged Fe(III) porphyrins, the increase in catalytic activity was temperature-dependent, whereas in a material built with a metal-free porphyrin and a Fe(III) porphyrin, the activity was dependent on visible-light irradiation. This latter material shows the highest catalytic activity after an induction time, with K 1  = 388 min −1 ·g −1 and a good performance after reuse studies. Graphical abstract: Image 1 Highlights: Supramolecular structures carrying Fe(III) porphyrins were prepared by ionic self-assembling. Nanostructured binary materials were obtained in an eco-sustainable way. The materials were efficient biomimetic catalysts in the reduction of 4-nitrophenol. The catalytic activity of the structures enhanced significantly under solar light. Best activity was observed for a material carrying metal-free porphyrins and Fe(III) porphyrins.